ANALISA KADAR BESI (Fe) DALAM AIR DI DEPOT AIR MINUM ISI ULANG YANG BERADA DI KELURAHAN DWIKORA KECAMATAN MEDAN HELVETIA KOTA MEDAN TAHUN 2021 - Megawati Zendrato; Dyna Grace Romatuan Aruan (JURNAL KIMIA SAINTEK DAN PENDIDIKAN, 2021)
Water is a very vital element for human life on this earth. In the human body about 50 -80% consists of water. The high demand for drinking water, especially in urban areas, has encouraged the emergence of bottled water product industries and the production of refilled drinking water depots. Re-drinking water is one type of drinking water that can be drunk directly without cooking it because it goes through certain processing processes such as drinking water that is safe for health, it must go through the physical, microbiological, chemical and radioactive requirements contained in it. mandatory and additional parameters. The purpose of this study was to determine whether the level of iron (Fe) in refill drinking water in Dwikora Village, Medan Helvetia District, Medan City was in accordance with what had been determined by the Minister of Health of the Republic of Indonesia. through Permenkes No. 492/Menkes/Per/IV/2010 concerning Drinking Water Quality Requirements. This research is descriptive and uses atomi c absorption spectrophotometer (AAS). Based on the results obtained from 10 samples of refill drinking water, it was shown that there were 2 samples (20%) of Fe content that did not meet the drinking water quality requirements obtained from depots E and F of 0.59 mg/l. and 0 respectively. 0.35 mg/l and 8 samples (80%) were obtained from the depot A = 0.22 mg/L, B = 0.10 mg/L, C = 0.28 mg/L, D = 0.19 mg/L L, G= 0.27 mg/L, H= 0.23 mg/L, I = 0.19 mg/L, J= 0.17 mg/L these levels stillmeet the drinking water quality requirements. The maximum limit for Fe levels in Drinking Water Quality Requirements As regulated in the Regulation of the Minister of Health No.492/Menkes/Per/IV/2010 is 0.3 mg/L.